Sodium content in processed food items in Sweden compared to other countries: a cross-sectional multinational study - Karlsson, Karin; Rådholm, Karin; Dunford, Elizabeth; Wu, Jason H. Y.; Neal, Bruce; Sundström, Johan (Frontiers in Public Health, 2023)
Background Dietary sodium has a dose-response relationship with cardiovascular disease, and sodium intake in Sweden exceeds national and international recommendations. Two thirds of dietary sodium intake comes from processed foods, and adults in Sweden eat more processed foods than any other European country. We hypothesized that sodium content in processed foods is higher in Sweden than in other countries. The aim of this study was to investigate sodium content in processed food items in Sweden, and how it differs from Australia, France, Hong Kong, South Africa, the United Kingdom and the United States. Methods Data were collected from retailers by trained research staff using standardized methods. Data were categorized into 10 food categories and compared using Kruskal-Wallis test of ranks. Sodium content in the food items was compared in mg sodium per 100 g of product, based on the nutritional content labels on the packages. Results Compared to other countries, Sweden had among the highest sodium content in the “dairy” and “convenience foods” categories, but among the lowest in “cereal and grain products,” “seafood and seafood products” and “snack foods” categories. Australia had the overall lowest sodium content, and the US the overall highest. The highest sodium content in most analyzed countries was found in the “meat and meat products” category. The highest median sodium content in any category was found among “sauces, dips, spreads and dressings” in Hong Kong. Conclusion The sodium content differed substantially between countries in all food categories, although contrary to our hypothesis, processed foods overall had lower sodium content in Sweden than in most other included countries. Sodium content in processed food was nonetheless high also in Sweden, and especially so in increasingly consumed food categories, such as “convenience foods”.